Tobacco contractual arrangements in Malawi and their impact on smallholder farmers: Evidence from Burley Tobacco contracts - Shaba, Abel Kondwani; Edriss, Abdi Khalil; Mangisoni, J. H.; Phiri, M. A. R. (International Food Policy Research Institute, 2017)
Contract farming is emerging as an important governance structure in certain agricultural value chains. This study was done with the objectives of understanding the contractual relations between buyers and small-scale growers in the tobacco industry in Malawi and the impact of contract farming on smallholder incomes. Cross-sectional data was collected from 211 contract and 109 non-contract smallholder burley tobacco farmers who sold tobacco in the 2012/13 season. Two analyses were undertaken. First, the study analyzed the contractual arrangement and the performance factors under contract using analytical methods from transaction costs economics. Commercial banks, through the tobacco buyer, provide farmers with input loans, which farmers use to obtain fertilizer, seed, and extension services, all of which are important to increase tobacco productivity. The results of the contract analysis indicated that side-selling, information asymmetry, moral hazard, and strategic contract default by farmers were some of the transactions costs that affect the success of contract farming. However, the contractual arrangement also contributed to reduced transfer costs and reduced the rejection rate for the tobacco produced by the contract farmers. Moreover, to the buying company, contract farming contributes to reduced monitoring costs, as farmers work in groups and monitor each other’s activities, such as baling of the tobacco leaf, which ensures better quality tobacco being offered under contract. Secondly, for the impact evaluation of contract tobacco farming, a treatment effect model was used. The study analyzed the factors that affect farmers’ participation in contract farming and the effect of that participation on net tobacco income. Landholding size, access to extension services, distance to the auction floor, and the gender of the tobacco farmer were found to strongly affect the participation decision. Differences in income between contract and non-contract farmers were found to be strongly influenced by landholding size and monitoring of sales at the auction. Contract participation increases tobacco income by 46.6 percent. This finding justifies making efforts to contractually link more smallholder farmers to tobacco companies. Therefore, a policy needs to be in place to facilitate such contracts between small-scale farmers and companies that buy tobacco leaf in Malawi.